Motor performance of children with attention deficit hyperactivity disorder: focus on the Bruininks-Oseretsky Test of Motor Proficiency - Khushboo Prashant Adhvaryu; Suruliraj Karthikbabu; Pratiksha Tilak Rao (The Korean Pediatric Society, 2022)
The literature review aimed to analyze studies assessing the motor abilities of children with attention deficit hyperactivity disorder (ADHD) using the Bruininks-Oseretsky Test of Motor Proficiency (BOTMP). The PubMed, OVID, Cochrane, and PEDro databases were searched for relevant articles published between February 2003 and September 2021. Despite the retrieval of limited studies, most included in this review were of fair to good quality. The diagnostic criteria for ADHD adhered to Diagnostic and Statistical Manual of Mental Disorders standards. The BOTMP has been used diversely in various countries, has been translated into various languages, is administered by various qualified medical professionals on children with variants of ADHD, with the long form of the tool used more widely than its short form. The motor performance of children with ADHD was better than that of children with other developmental disorders, but children with ADHD underperformed compared to their age-matched typically developing peers. Although the BOTMP tool has been widely used to evaluate the motor performance of children with various disabilities, our understanding of the motor repertoire of children with ADHD is inadequate. Future research can aim to use the BOTMP to better understand the motor repertoire of children with ADHD to aid their overall rehabilitation.